The Effect of Job Insecurity on Innovative Work Behavior through Organizational Commitment in UFO Elektronika Employees - Dian Fauziawati (Profesional Muda Cendekia Publishing, 2021)
UFO Elektronika is a brand used by PT Damai Sejahtera Abadi, company engaged in furniture and electronic retail, which was founded in 2003. This study aims to determine and explain the effect of job insecurity on innovative work behavior with organizational commitment as an intervening variable on UFO Elektronika employees. This is a quantitative study with a sample of 41 employees using the saturated sampling technique. The statistical analysis used SEM-PLS with SmartPLS 3 software. The results explained that job insecurity has a negative significant effect on organizational commitment, job insecurity has a negative significant effect on innovative work behavior, organizational commitment has a positive significant effect on innovative work behavior, and organizational commitment are able to mediate the relationship between job insecurity and innovative work behavior. The implementation of research that can be applied to companies is the creation of a suggestion box that can be filled in by employees to report conditions in the workplace to minimize work insecurity caused by several factors and communicate problem solving together, compile an organizational culture to strengthen the bonds of value, company values for employees, and rewarding employees who are active in proposing innovative ideas for the success of the company.